Industrialization and the state : (Harvard Institute for International Development, 2001)
This study demonstrates that Taiwan policymakers varied their approach to development as circumstances changed. Export promotion of labor-intensive industries, which predominated in the 1960s, was supplemented by efforts to promote import-substituting heavy industries in the 1970s. In the early 1980s there was a fundamental change in the economic environment as Taiwan's government reduced its active intervention in the economy and created a foundation for development based on information and other high-technology products. Taiwan's economy continued to prosper in the 1990s because policies and systems changed along with conditions